Understanding consumers ' purchasing behavior towards online shopping in Kuching / Andrea Rachel Elone - Elone, Andrea Rachel (2015)
The Internet, also addressed as the World Wide Web (www), has undeniably given a big impact on social, organization and public affairs worldwide (Jeacle & Carter, 2011) The breakthrough of the Internet had changed and formed new methods in the management of organizations. The Internet has become a medium through which organizations section their markets, distinguish and allocate their products and communicate with stakeholders (Dobre & Milovan-Ciuta, 2015). It has made the world seem smaller in size as most information on product and services are accessible easily as long as one has an Internet connection. Today, the Internet is not only a networking media, but it is also used as a means of transaction for consumers at global market.